PENGARUH PENAMBAHAN PEKTIN TERHADAP MUTU SELAI JAGUNG MANIS (ZeaMays.L). - Rianto, Rianto; Efendi, Raswen; Zalfiatr, Yelmirai (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this study was todetermine the effect of pection additionÂ  on quality of sweet corn jam. This study uses a Completely Randomized Design (CRD) with 4 treatments and 4 replications. The treatment were jam without and with addition of pection 0,5%, 1%, and 1,5%, Data were statistically analyzed using analysis of varianca (ANOVA) and Duncan's New Multiple Range Test (DNMRT) at 5% level. The results showed that the addition of pectin significantly effected water content, ash content, total soluble solids and organoleptic assessment. The best treatment from this results was 0,5% pectionaddtion with water content of 31.74%, ash content of 0.71%, , total soluble solids 72.67 brix, crude fiber content of 0.66%, with description of jam from the best treatment was taste of sweet corn, flavorful sweet corn, yellow and overall assesment showed that the jam.Â Keywords: Jam, Pectin and Sweet Corn.